Aqueous colloidal processing and green sheet properties of lead zirconate titanate (PZT) ceramics made by tape casting - Navarro, A.; Alcock, Jeffrey R.; Whatmore, Roger W. (Elsevier Science B.V., Amsterdam., 2004)
An aqueous system for tape casting PZT ceramics was developed using poly (vinyl alcohol) binder, poly (propylene glycol) plasticizer, D3021 dispersant and Surfynol SE-F wetting agent. Screening experiments were performed to assess the stability of the suspension in the presence of the dispersant by performing pH, conductivity and Zeta potential measurements. Viscosity measurements were used to find the optimum level of dispersant needed to produce a stable slip at pH 10.2. Subsequently, the rheological and mechanical characteristics were also investigated.
Keywords: Tape casting; PZT; Zirconate; Titanate